Sustainable development, poverty eradication and macro/micro policy adjustments - Singh, Naresh (International Institute for Sustainable Development WinnepegCA)
Defines the operational concept of sustainable development. Establishes the integrated linkages between sustainable development, poverty eradication and macro-micro policy adjustment. Surveys the macro-micro policy investments used by the World Bank and the IMF in the course of structural adjustment.